Improving Recruitment Procedures for School‐Based Surveys: Through the Lens of the Illinois Youth Survey - Clary, Kelly Lynn; Reinhart, Crystal A.; Kim, Hyun Jung; Smith, Douglas Cary (The Journal of school health, 2021)
ABSTRACT BACKGROUND Epidemiological surveys are designed to collect representative trend data. School‐based surveys are important to utilize so systems can effectively create prevention and intervention programs to alter youths' perceptions and behaviors related to substance use. However, there are many barriers when implementing a school‐based survey. METHODS This mixed methods study sought to uncover 30 school personnel's challenges when making the decision to implement the Illinois Youth Survey (IYS). Through a descriptive and interpretive approach, participants' thoughts to improve future recruitment procedures and reduce barriers for implementation were analyzed. RESULTS Results found challenges included: (1) time; (2) parent‐opt out consent letter; (3) wording of the survey responses; (4) honesty of the students' responses; (5) importance and use of the data. Moreover, the most common suggestions to improve recruitment included: (1) sharing knowledge about trend data; (2) year‐round communication with school personnel; (3) targeting school personnel groups; and (4) providing examples of data use. CONCLUSIONS Findings can be used to improve recruitment procedures for others who have similar challenges. If schools, counties, and states have representative data they can more precisely tailor their programming to meet the needs of their population.